The Effect of Cultivation Site Altitudes on the Quality Parameters of Meniran (Phylanthus niruri L.) - Wahyuni, Dinar Sari C.; Pangestika, Maya Widia; Andriyani, Della; Rinanto, Yudi; Fatimah, Siti (Majalah Obat Tradisional, 2023)
Meniran (Phyllanthus niruri L.) is known as a medicinal plant for immunomodulatory, hypoglycemic, diuretic treatment, and kidney disorders. It has phenolic and flavonoid as the active compounds. Several commercial products utilize meniran as the main ingredient for immunomodulators. However, the standard raw material for production has not been well reported. The study aimed to standardize the quality of meniran’s raw materials from different locations and altitudes. The phenolic compounds as the active component and their antioxidant activity were further studied. The raw materials were collected from Sukoharjo, Jember, and Karanganyar which are located from 104 masl, 243 masl, and 722 masl. The specific and non-specific standardization based on Indonesian Herbal Pharmacopoeia were investigated. The antioxidant activity was investigated. It resulted in the specific and non-specific parameters that were according to standard except for the acid soluble ash test from the Jember sample which was much higher (6.333% ± 0.969) than the standard (<1.2%). In addition, the flavonoid (1.529 ± 0.167%w/w) and phenolic (1.65 ± 0.006 %w/w) content showed that the sample collected from Jember was significantly higher than other locations. However, the strongest antioxidant activity was in the sample collected from Sukoharjo (IC50 101.84μg/mL). On the other hand, there was no correlation between the total flavonoid and the total phenolic to antioxidant activity in this plant. It suggested that the antioxidant activity in these plants did not depend on the flavonoid and phenolic compounds. In conclusion, the raw material of meniran (Phyllanthus niruri L.) collected from 3 different altitudes showed the quality of herbal medicine of mainly non-specific parameters and met the requirements of Indonesian Herbal Pharmacopoeia. The total phenolic and flavonoid as the active substances varied through all 3 different altitudes. It was in line with the antioxidant activity which varied to all 3 different altitudes due to the phytochemical profile variety.